Perfluorosulfonyl Imide versus Perfluorosulfonic Acid Ionomers in Proton‐Exchange Membrane Fuel Cells at Low Relative Humidity. Issue 3 (7th January 2020) - Nguyen, Huu‐Dat; Porihel, Regis; Brubach, Jean‐Blaise; Planes, Emilie; Soudant, Priscillia; Judeinstein, Patrick; Porcar, Lionel; Lyonnard, Sandrine; Iojoiu, Cristina
Abstract: Designing highly conductive ionomers at high temperature and low relative humidity is challenging in proton‐exchange membrane fuel cells. Perfluorosulfonyl imide ionomers were believed to achieve this goal, owing to their exceptional acidity and excellent thermal stability. Perfluorosulfonyl imide ionomers are less conductive than the analogous perfluorosulfonic acids despite similar membrane microstructure. In this study, the distinct behavior is rationalized by in situ synchrotron infrared spectroscopy during hydration. The protonation mechanism, formation of the protonic moiety and water clustering are totally different for the two different families of membranes. The ionization mediated by trans ‐to‐ cis conformational transition of the perfluorosulfonyl imide ionomer is not accompanied by the formation of hydronium ions. In contrast, Zundel‐ion entities were identified as the elementary protonic complex, which is stable over the hydration range. The H‐bond network of surrounding water molecules appears to be less connected and the protons remain highly localized and unavailable for efficient structural transport. The delocalization of protons and their mitigated interaction with the surrounding medium are prominent effects that negatively impact conductivity. Abstract : Battle of the acids : The impact of acidic terminating functions, namely perfluorosulfonic and perfluorosulfonyl imide acids, on the properties of proton‐conducting block copolymers applicable as fuel cell electrolytes is described. Although hyperacidity was believed to promote conductivity, it is concluded that delocalization of protons and mitigation of interactions with the surrounding medium are of primary importance to obtain best‐performing ionomers.